2000
DOI: 10.1002/1522-2675(20000906)83:9<2436::aid-hlca2436>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Planar Chiral (Arene)tricarbonylchromium Complexes via Enantioselective Deprotonation by Conformationally Constrained Chiral Lithium-Amide Bases

Abstract: Dedicated to Professor Albert Eschenmoser on the occasion of his 75th birthday Enantioselective lithiation/electrophile addition reactions with eight chiral Li-amide bases, 1 ± 8, and five [Cr(arene)(CO) 3 ] complexes, 9 ± 13, were investigated. Restriction of conformational freedom in the chiral Liamide base Li-1, in general, did not result in an increase in asymmetric induction. A new route to enantiomerically enriched (75 ± 92%) planar chiral ortho-substituted benzaldehyde complexes via enantioselective lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…After the phenol hydroxy groups of 2 were protected as the corresponding methanesulfonates, we first attempted various catalytic asymmetric reduction of 3 and found that (À)-(Ipc) 2 BCl gave optically active 4 with excellent enantio-and diastereo-selectivities, and good chemical yield (99% ee, anti/syn P 99:1, 68%) [15]. However, the methanesulfonylation of 4 followed by the treatment with 2-picolylamine led to a 1:2 mixture of dl-and meso-2,6-disubstituted piperidine derivative 5.…”
Section: Resultsmentioning
confidence: 99%
“…After the phenol hydroxy groups of 2 were protected as the corresponding methanesulfonates, we first attempted various catalytic asymmetric reduction of 3 and found that (À)-(Ipc) 2 BCl gave optically active 4 with excellent enantio-and diastereo-selectivities, and good chemical yield (99% ee, anti/syn P 99:1, 68%) [15]. However, the methanesulfonylation of 4 followed by the treatment with 2-picolylamine led to a 1:2 mixture of dl-and meso-2,6-disubstituted piperidine derivative 5.…”
Section: Resultsmentioning
confidence: 99%
“…13 C NMR (50 MHz, C 6 D 6 ): δ = –7.0, 91.3, 95.3, 98.0, 98.2, 99.7, 101.7, 191.8, 231.7 ppm. [α] D 21 = +440 ( c = 0.0005, toluene) for 91 % ee [ref 8h. [α] D 21 = +354 ( c = 0.006, CHCl 3 ) for 73 % ee ].…”
Section: Methodsmentioning
confidence: 99%
“…Optimization studies are also performed on benzylic protons. ketones [4c,e,j,o,p,q,r,s, 20-28], (iii) the deprotonation of bridgehead carbons followed by either trapping with an electrophile or β-elimination (and thus a ring opening) [4b,g,h,i,k,l,n, [29][30][31][32][33][34], and (iv) the deprotonation of arylic appendages, directly on the aryl moiety or its benzylic position [4f,m, [35][36][37][38][39]. Few other types of transformations have also been explored, which are mentioned at the end of this chapter [40][41][42][43].…”
Section: Chiral Lithium Amides As Basesmentioning
confidence: 99%
“…The same CLA and electrophile were used with LiCl to achieve the asymmetric desymmetrization (ee up to 98%) of bicyclic derivative 141 into α-trimethylsilyldiketone 142 (Scheme 10.8, middle) [33]. Ring opening can be consecutive to the bridgehead deprotonation as observed for (i) the symmetrical ring-fused episulfoxide 143 that gave, after reacting with the base (CLA 18a or 24a, 1.2 equiv), the enantioenriched (ee up to 82%) alkenyl sulfoxide 144 (Scheme 10.8, bottom left) [34] 5a, 6a, 18a, 64-68, 1.1 equiv) has been explored from five [Cr(arene)(CO) 3 ] complexes (152-156, Scheme 10.10, top) [37]. Five planar chiral ortho-substituted complexes were isolated with good ee (up to 92%).…”
Section: Enantioselective Deprotonation Of Bridgehead Carbonsmentioning
confidence: 99%